2018
DOI: 10.1038/s41598-018-20670-0
|View full text |Cite
|
Sign up to set email alerts
|

Escaping the Ashby limit for mechanical damping/stiffness trade-off using a constrained high internal friction interfacial layer

Abstract: The development of new materials with reduced noise and vibration levels is an active area of research due to concerns in various aspects of environmental noise pollution and its effects on health. Excessive vibrations also reduce the service live of the structures and limit the fields of their utilization. In oscillations, the viscoelastic moduli of a material are complex and it is their loss part – the product of the stiffness part and loss tangent – that is commonly viewed as a figure of merit in noise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
(32 reference statements)
6
21
0
Order By: Relevance
“…In the current study we have used the conclusions of this previous work and have used the 'nlayered' micromechanical model to produce numerical predictions of the storage shear modulus and tan of appropriate idealised composite microstructures in an effort to gain insight into the relationship between the morphology and mechanical behaviour of our samples. This strategy is strengthened by another recent study [13], where we showed excellent predictions of the experimental behaviour using the same Barium titanate beads used here, but spray coated with a different viscoelastic polymer and then incorporated in the same polystyrene matrix [13]. In that study, very close agreement was found between the experimental measurements and the numerical micromechanical predictions, giving us confidence to follow the same strategy with the materials in this study.…”
Section: Numerical Modellingsupporting
confidence: 82%
See 4 more Smart Citations
“…In the current study we have used the conclusions of this previous work and have used the 'nlayered' micromechanical model to produce numerical predictions of the storage shear modulus and tan of appropriate idealised composite microstructures in an effort to gain insight into the relationship between the morphology and mechanical behaviour of our samples. This strategy is strengthened by another recent study [13], where we showed excellent predictions of the experimental behaviour using the same Barium titanate beads used here, but spray coated with a different viscoelastic polymer and then incorporated in the same polystyrene matrix [13]. In that study, very close agreement was found between the experimental measurements and the numerical micromechanical predictions, giving us confidence to follow the same strategy with the materials in this study.…”
Section: Numerical Modellingsupporting
confidence: 82%
“…But most importantly, as is found in this current work, on incorporation of a rigid particle (either spheres or fibres) a thin layer of the SIS copolymer is seen to form on the surface of the particles, see Fig. 1, effectively producing a coated particle as investigated and described in our previous work [13].…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations